Dead heat [compact disc, unabridged] - Rosenberg, Joel C., 1967- (Brilliance Audio, 2007)
In the midst of a world ready to explode, and the current President of the United States leaving office the political battle for the most influential job in the world is in a dead heat. When the Secret Service learns of a terrorist plot to assassinate one of the candidates, the heat rises as they try to figure out which candidate is the target.